Public records online : the national guide to private and government online sources of public records - Sankey, Michael L., 1949-; Flowers, James R. (James Robert), 1973- (Online ease., 1999)
A national directory to government agencies and private companies that furnish online automated public record information, maintain proprietary public record databases, and offer CD-ROMs.